Information Affecting Crisis Management and Business Continuity in Indian Manufacturing Industries - Singh, Amarpreet (Digital Repository of Theses - SSBM Geneva, 2024)
This study provides an in-depth analysis of information management practices in the Indian manufacturing sector, focusing on their impact on crisis management and business continuity. The primary objective is to understand how information quality and timeliness influence crisis response effectiveness. The research employs a mixed-methods approach, combining qualitative and quantitative methodologies. Qualitative data is gathered through in-depth interviews and focus group discussions with key industry stakeholders, offering rich, detailed insights into their experiences and perceptions of information management during crises. The quantitative aspect involves surveys using predefined scales to collect and analyze data, providing a broad statistical overview. The study objectives are to evaluate the nature and effectiveness of information management practices, such as real-time data collection, verification techniques, and collaborative information sharing, employed by manufacturing organizations. It also aims to assess the perceived impact of information accuracy and timeliness on crisis management effectiveness and business continuity. The research explores the challenges the manufacturing industry faces in maintaining information accuracy and timeliness during crises and examines the advantages of real-time data collection and other strategies. Methodological rigor is ensured by addressing potential threats to validity, including external, internal, and construct validity. Ethical considerations, such as obtaining informed consent, ensuring privacy and confidentiality, and securing necessary approvals, are integral to the research. The findings reveal a significant relationship between information accuracy, timeliness, crisis management practices, and business continuity outcomes. The statistical analysis shows that for every 1% increase in information accuracy, there is an associated 0.85% improvement in crisis management effectiveness (p < 0.01). For every 1% increase in information timeliness, there is an associated 0.78% improvement in business continuity outcomes (p < 0.01). These results underscore the crucial role of accurate and timely information in effective crisis management and operational resilience. The study also highlights the importance of contextual factors such as organizational culture, leadership style, and technological infrastructure in shaping the effectiveness of information management practices. This research contributes both theoretically and practically to the field of crisis management. It provides practical recommendations for industry practitioners to enhance crisis response capabilities and operational continuity, ultimately bolstering the competitiveness and resilience of Indian manufacturing industries. The insights are intended to align theoretical knowledge with practical implications, offering a comprehensive contribution to the understanding and improvement of crisis management practices in the manufacturing sector.